TRANSPORT AND OPERATIONAL STATE OF REPUBLIC MOTOR ROAD NETWORK AND MAIN DIRECTIONS OF THEIR QUALITY IMPROVEMENT - I. I. Leonovich; Y. Y. Novgorodsky; I. V. Burtyl (Наука и техника)
The paper considers problems pertaining to evaluation of pavement smoothness and pavement strength on motor roads of the Republic of Belarus. An analysis of dynamics concerning development of smoothness regression processes is given in the paper. The paper describes the existing methods for evaluation of strength within the framework of modern investigations. Principles of designing non-rigid motor roads are comprehensively studied in the paper. The paper proposes a dependence between pavement strength and pavement smoothness.